Search for the rare charmless hadronic decay B+-> a(0)(+)pi(0) - Aubert, B; Bona, M; Boutigny, D; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; et al. (2008)
We present a search for B decays to a charged scalar meson a0+ and a π0 where the a0+ decays to an η meson and a π+. The analysis was performed on a data sample consisting of 383×106 BB̄ pairs collected with the BABAR detector at the PEP-II asymmetric-energy B Factory at SLAC. We find no significant signal and set an upper limit on the product branching fraction B(B+→a0+π0)×B(a0+→ηπ+) of 1.4×10-6 at the 90% confidence level. © 2008 The American Physical Society.